Determination of effect of elliptic notches and grooves on stress concentration factors on notched bar in tension and grooved shaft under torsion - Ahsan, Rumman Ul; Prachurja, Protyasha; Ali, Abu Raihan Mohammad; Mamun, Mohammad Arif Hasan (Journal of Naval Architecture and Marine Engineering, 2013)
Stress concentration of structural members can be reduced considerably by the judicious choice of elliptic shaped stress raisers like notch and groove. Substantial effort has been given by numerous researchers to accurately measure the effect of such stress raisers, particularly of semicircular shaped notch and groove. An exhaustive bibliographical study proved that there is scope to investigate further and establish an alternative design criteria; concerning the elliptic geometry. Computational method, primarily the finite element method has been used to analyze the models under loading. This paper suggests the use of a modified elliptic shape which gives less stress concentration when compared to semicircular notch and groove. The ratio of minor and major half axes of the ellipse should be between 0.3 and 0.4. The introduction of shoulder with elliptic notch and groove even reduces the stress concentration. The results obtained from FEM analysis propose optimal values of geometrical design parameters. The study represents not only a precise view of stress distribution, but also to develop charts that can be used by designer for practical purposes. DOI: http://dx.doi.org/10.3329/jname.v10i1.13675